Socio-Economic and Spatial Correlations of the Eastern European Health Paradox in Hungary - Zoltán Egri; Tamás Tanczós (DETUROPE)
This paper describes the Hungarian aspects and the latest results of the so-called Eastern European health paradox in terms of (micro-)regions. In particular, this paper aims at highlighting the spatial correlations of premature mortality and the main causes of death by gender as well as their socio-economic and spatial embeddedness. The tool for our study is represented by exploratory spatial data analysis (ESDA): the main health inequalities of Hungary’s micro-regions are described with the use of global autocorrelation tests as well as regression models suitable for the identification of general and spatial features. According to our findings, the causes of premature death are characterised by a marked spatial determination for both genders but mostly for men. The regression models of the causes of premature death have confirmed that neighbourhood relations and micro-regional inequalities in issues like the level of socio-economic development, settlement structure, lifestyle, social capital, healthcare infrastructure or social deprivation have substantial impacts on mortality in a given area in the case of men. These findings are also true for women, except for one issue: neighbourhood assimilation. It should be noted in view of our research findings that, in addition to socio-economic explanatory factors, spatiality (belonging to a region) is a major explanatory factor regarding the micro-regional inequalities of premature mortality. In particular, Borsod-Abaúj-Zemplén county, known as a former industrial base, should be noted here; this county is a significant and complex crisis area with regard to the health status of both genders in Hungary today. As a short-term measure for the improvement of spatial health status, the development of health awareness and the mitigation of psychosocial stress (by civil organisations) are suggested.